Espresso Coffee for the Treatment of Somnolence in Parkinson’s Disease: Results of n-of-1 Trials - Ferreira, Joaquim J.; Mestre, Tiago; Guedes, Leonor Correia; Coelho, Miguel; Rosa, Mário M.; Santos, Ana T.; Barra, Márcio; Sampaio, Cristina; Rascol, Olivier (Frontiers in Neurology, 2016)
There is limited information available concerning the treatment of daytime somnolence associated with Parkinson’s disease (PD); the most frequently applied therapeutic strategies include decreasing the dose of dopamine agonists or adding potential wake-promoting agents. There is recent data from a placebo-controlled trial concluding on a non-significant trend in favor of caffeine. We aimed to evaluate the efficacy of espresso-coffee in the treatment of daytime somnolence in PD. To evaluate the efficacy of espresso-coffee in the treatment of daytime somnolence in PD, we have conducted multiple single-patient (n-of-1) clinical trials comparing regular espresso coffee to decaffeinated coffee in PD patients presenting moderate to severe daytime somnolence defined as an Epworth Sleepiness Scale (ESS) score >9. Each single-patient (n-of-1) trial included a sequence of three crossovers (two treatment periods separated by two days of washout). Four patients were included in the studies and three completed the three pairs of treatment periods. In two of the four patients, espresso coffee was considered beneficial. This study concludes that multiple single patient trials are feasible in PD and suggests that espresso-coffee may have a beneficial effect on daytime somnolence in some patients. These results cannot be generalized beyond the patients included in these trials.